Respiratory and gastrointestinal dysfunctions associated with auriculo‐condylar syndrome and a homozygous PLCB4 loss‐of‐function mutation. Issue 6 (23rd March 2016) - Leoni, Chiara; Gordon, Christopher T.; Marca, Giacomo Della; Giorgio, Valentina; Onesimo, Roberta; Perrino, Francesca; Cianfoni, Alessandro; Cerchiari, Antonella; Amiel, Jeanne; Zampino, Giuseppe
Abstract : Auriculo‐Condylar Syndrome (ACS) is a craniofacial malformation syndrome characterized by external ear anomalies, hypoplasia of the mandibular condyle, temporomandibular joint abnormalities, micrognathia, and microstomia. Glossoptosis, masticatory abnormalities, orthodontic problems, and malocclusion occur in a majority of affected subjects. The clinical diagnosis is usually suggested by the pathognomonic ear appearance ("question mark ear"), consisting of a variable degree of clefting between the helix and earlobe. The genetic mechanisms underlying ACS have recently been identified. Both autosomal dominant and recessive inheritance of mutations in phospholipase C, beta 4 ( PLCB4 ) and endothelin 1 ( EDN1 ) have been reported along with autosomal dominant mutations in guanine nucleotide‐binding protein (G protein) α inhibiting activity polypeptide 3 ( GNAI3 ). We report 6 years of follow‐up of a child with a clinical phenotype consistent with ACS due to a homozygous frameshift mutation in PLCB4 . The baby presented feeding difficulties associated with failure to thrive and a complex sleep‐related respiratory disorder, characterized by central and obstructive apnoeas. Our observations of this case further delineate the phenotype of ACS associated with autosomal recessive PLCB4 loss‐of‐function mutations, underscoring gastrointestinal dysfunction and severe sleep‐related breathing abnormalities as additional features when compared to patients with heterozygous mutations with a presumed dominant negative effect. © 2016 Wiley Periodicals, Inc.